Neanderthal Lifeways, Subsistence and Technology One Hundred Fifty Years of Neanderthal Study - Conard, Nicholas J.; Richter, Jürgen (Vertebrate Paleobiology and Paleoanthropology, 2011)
The 150th anniversary of the discovery of the famous Neanderthal fossils gave reason for an international and interdisciplinary symposium in Bonn/Germany. The present book arose from this congress and focuses on multiple aspects of archaeological investigation on Neanderthal lifeways. In-depth studies of top-ranking scientists provide a detailed and comprehensive survey of contemporary research on our Pleistocene relatives. Examinations and debates are embedded in a variety of regions and time frames. Chronology, subsistence, land use, and cultural adaptations among late Neanderthals form the major trajectories of the book. The wide range of approaches involved, leads to an increasing understanding of the facets of and the variability of Neanderthal behavioural patterns.   The present volume is complemented by a paleontologically orientated publication of the same congress (edited by Gerd-Christian Weniger and Silvana Condemi).